Heurística poético-semiótica a possibilidade de uma experiência artística e estética no ensino médio - Cristo, Rodrigo Fagundes de (2006)
This research is based on Arts and Education Research Field and its main goal is investigate the process of criation and meaning, based on a significant educational practice, integrating the knowledge of contemporary visual production with references that come from the reality of the subjects. Those are learners of Primary School. This research, made in a context of formal teaching, intented the contact with the problematic that involves the integrations of the sensitive and intelligible dimentions in those process. By means of those dimentions, the poetical and the meaning are ways to installate the autonomy of the citizen in formation. Under the shadow of those two fields, the theoretical reflection is founded in Gaston Bachelard's Poetic Filosofy studies and in Algirdas Greimas's semiotic narrative analyses project, to constitute a structure of meaning constructed by the learners. The methodological approach is qualitative, applying the participative observation, field diary, semi-plained enterview and documental analyses as instruments. With the results was verified how the learners could develop the process of criation and meaning contextualized in their interest focus, criating and analysing visual texts.